Pengaruh Pembelajaran Matematika Realistik Terhadap Kemampuan Komunikasi Matematis Siswa Kelas VII SMP - Sihotang, Ida Wati (Unika Santo Thomas Medan, 2019)
This study aims: (1) To find out whether the Realistic Mathematics Learning approach influences students' mathematical communication skills. (2) To find out whether the increase in students' mathematical communication skills with the Realistic Mathematics Learning approach is higher than conventional learning. This type of research is experimental research using pretest-posttest control group design. The study population was all VII grade students of YPAK Galang SPM consisting of three classes. The research sample was selected using simple random sampling technique, so that the VII-A class as the experimental class and VII-C class as the control class were obtained with 37 students each. The data used in this study are quantitative data. Based on the analysis of the research data, the following results are obtained: (1) the results of the regression analysis obtained by the equation (Y) Ì‚ = 36,945 + 1,003X. And from the results of the correlation obtained that Realistic Mathematics Learning has a positive effect with a correlation coefficient of 0.944 and a coefficient of determination of 89.1%. So it can be concluded that Realistic Mathematics Learning influences students' mathematical communication skills. ; (2) the results of the t-test analysis with the value of t count = 4.489 and t table = 1.666 which means t count> t table, then the hypothesis Ho is rejected. So it can be concluded that the mathematical communication skills of students taught by Realistic Mathematics Learning are higher than the mathematical communication skills of students who are taught by conventional learning.